Male sex pheromone in the parasitoid wasp Nasonia longicornis: Chemical and behavioral analyses - Kurtanovic, Alisa; Hofferberth, John; Ruther, Joachim (Frontiers in Ecology and Evolution, 2022)
The use of sex pheromones for the attraction of potential mating partners is widespread in insects. Species specificity of the chemical signals is indispensable, particularly in closely related species with overlapping habitats. In parasitoid wasps of the genus Nasonia, it is the males that produce sex pheromones in their rectal vesicles. The genus consists of four species: N. vitripennis (Nv), N. giraulti (Ng), N. oneida (No), and N. longicornis (Nl). The cosmopolitan species Nv is sympatric with Ng and No in eastern North America and with Nl in the west. Interspecific courtship is common in Nasonia although hybridization is prevented in most combinations by Wolbachia-mediated cytoplasmic incompatibility. The pheromone of Nv males differs from all congeneric species by an additional component that is believed to ensure precopulatory isolation from the sympatric congeners. Detailed investigations on these interactions, however, exist only for the species combination Nv/Ng. Here we report the results of chemical and behavioral investigations on the male sex pheromone of Nl. The pheromone consists of (4R,5S)-5-hydroxydecanolide (RS) and a minor component 4-methylquinazoline (MQ) which are produced only after eclosion. Pheromone titers maximized two days after eclosion and remained constant on day three. The pheromone is deposited by abdomen dipping which was shown increasingly by males after mating or brief contact with a female. The presence of hosts containing females about to emerge did not increase marking behavior. Site fidelity of males at their own pheromone markings is mediated by MQ. Both natural and synthetic pheromone attracted virgin but not mated females and both RS and MQ are required for this attraction. Females collected during emergence from the host responded likewise to the pheromone showing that most of them emerge unmated. The addition of the Nv-specific component (4R,5R)-5-hydroxydecanolide (RR) to the Nl pheromone, however, disrupted the response of Nl females. The present study demonstrates that Nl uses the male sex pheromone in a similar way as previously shown for Nv and Ng. Furthermore, it shows that Nl females use the newly evolved Nv-specific pheromone component RR to avoid costly sexual interactions with Nv males in regions of sympatry.